Procurement design with loss averse bidders - Nicolas Fugger; Philippe Gillen; Tobias Riehm (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We show that it is beneficial for a buyer to conduct a multi-stage mechanism if bidders are loss averse. In a first step, we derive a revenue equivalence principle. Fixing the multi-stage structure, the revenue is independent of the chosen payment rule. Secondly, we introduce a simple two-stage mechanism which always leads to a decrease in procurement costs compared to any single-stage auction. Finally we derive the optimal efficient two-stage mechanism.
Keywords: D44; D47; D90; 330; Auctions; Experiment; Loss aversion; Preferences